The Legal Regime of the Strait of Hormuz and Attacks Against Oil Tankers: Law of the Sea and Law on the Use of Force Perspectives. (27th October 2022) - Lott, Alexander; Kawagishi, Shin
Abstract: The Strait of Hormuz has great significance for the world economy as an oil chokepoint. Yet in recent years, international navigation through the Strait of Hormuz has been repeatedly hampered and subject to discriminatory navigational restrictions and attacks. Such measures have been mostly aimed at oil tankers. This article examines the maritime incidents that occurred in the Strait of Hormuz in 2019: mine attacks against oil tankers and the arrest of an oil tanker by the Iranian armed forces. This study approaches these incidents from the perspectives of the law of the sea and from jus ad bellum .